Efficacy of Tranexamic acid and cell salvage in conserving blood in scoliosis surgery / Looi Ji Keon - Looi, Ji Keon (2018)
Part A - Tranexamic Acid given as single dose to reduce blood loss in scoliosis surgery is a higher dose range more superior? Scoliosis surgery is often associated with long operative times and extensive blood loss. Published studies consistently demonstrate the efficacy of tranexamic acid (TXA) to reduce intraoperative blood loss compared to placebo. However, the optimal dose to maximize its anti-fibrinolytic properties without increasing thrombotic complications remains elusive.This retrospective study compares the efficacy of two dose ranges of TXA in reducing intraoperative blood loss in posterior spinal fusion (PSF) surgery. 173 patients with adolescent idiopathic scoliosis (AIS) who underwent PSF in 2015 and 2016 were retrospectively studied. All patients received 1 gram of intravenous TXA without maintenance. They were divided into two groups ï¿½ Group A- High dose TXA (>20 mg/kg, n=115) and Group B- Low dose TXA (<20 mg/kg, n=58). Mean age, weight, blood volume, Cobbï¿½s angle and number of levels fused were 15.4 years, 41.8 kg, 2914.8 mls, 66.4o , 11.2 levels and 18.2 years, 57.5 kg, 3652.8 mls, 65.7o , 10.8 levels in Groups A and B respectively. In terms of mean absolute intraoperative blood loss (827.8 vs 909.4mls; p=0.26) and percentage of blood volume loss (28.5 vs 24.9%; p=0.11), the differences between the high and low dose groups did not achieve statistical significance. iv Total blood loss per segment (72.2 vs 81.1mls; p=0.08) and per screw (56.8 vs 63.8mls; p=0.14) also did not differ significantly between the groups and so did duration of hospital stay (3.4 days vs 3.4 days, p=0.96). No patients received allogenic blood transfusion and none developed thrombotic complications. Higher dose of TXA (>20 mg/kg), failed to demonstrate superiority in reducing blood loss compared to a lower dose of < 20 mg/kg when given as a single dose in PSF for AIS. Part B - A retrospective review of efficacy of cell salvage to conserve blood in scoliosis surgery Cell salvage is widely practised in scoliosis surgery to reduce allogenic transfusion. However, evidence is limited with regards to its efficacy. This study aims to determine the efficacy of intraoperative cell salvage in single-staged posterior spinal fusion surgery. 89 patients who underwent single-staged posterior spinal fusion for adolescent idiopathic scoliosis in 2016 were retrospectively studied. All patients received intraoperative cell salvage (ICS) as part of institutional protocol. Mean intraoperative blood loss was 909 mls. They were categorised into two groups ï¿½ Group C (< 900 mls blood loss, n=50) and Group D (> 900 mls blood loss, n=39). The mean age and weight was 16.1 years, 46.8kgs and 17.0 years, 49kgs for Group C and D respectively. Preoperative baseline characteristics such as blood volume (3121 vs 3346 mls), Cobbï¿½s angle (57.6o vs 66.8o ), number of levels fused (9.7 vs 12.4), number of screws (12.4 vs 15.3) were higher in Group D compared to Group C. Blood volume returned by ICS were 260 mls and 560 mls for Group C and D respectively. For both groups, 47% of total intraoperative blood loss was returned via ICS. Analysis of the pre-and postoperative haemoglobin levels did not show statistical significance between Groups C and D (preop: 13.4 vs 13.7 and postop: 11.1 vs 10.7 g/dL). None of the subjects received perioperative v allogenic blood transfusion or reported complications from the use of cell salvage. Intraoperative cell salvage is effective in conserving blood in posterior spinal fusion surgery. Post-operative haemoglobin levels did not differ significantly between the higher and lower blood loss groups.